Sovrapposizioni. Le immagini tra realtà, verità e azione - Tondo, Claudio (Scenari, 2021)
Images are a widespread presence appearing in a variety of forms, modes of employment, and mounts. They are neither casts nor simulacra, which dissolve reality in the self-referential and derealizing game of simulation and virtuality. On the contrary, images can enlarge the range of what is visible, providing the means for a technological modality of sight oriented to the strengthening of perception and to transparency. We are moving toward a mixed area of experience where maps overlap, communicate, coexist and permeate things. Images are an ontological force attesting the existence of what is concealed from view, a pragmatic and performative force guiding production and action and an epistemological force which “dares” to display truth.